PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DALAM MEMPERKUAT HUBUNGAN SISTEM PENGENDALIAN MANAJEMEN DENGAN PENCAPAIAN KINERJA PERUSAHAAN: SUATU TELAAH KEPUSTAKAAN - Karsam, Karsam; Leli Ravita Manurung, Ruth (Jurnal Riset Akuntansi dan Keuangan, 2014)
Management control system is one tool to implement strategies that can motivate all members of the organization to be able to achieve the goal. One of the important characteristics in applying management control system is the application of accountancy accounting. Accountability is based on the idea that a manager must be held accountable for his own achievements and achievements of his subordinates. Performance measurement and control systems are tools used by managers that are effective in achieving the expected goals and strategies. Thus the implementation of accountancy accountability will strengthen the relationship between management control systems with performance achievement.